Experimental Study on Fatigue Performance of Negative Bending Moment of Steel-Concrete Continuous Composite Box Girder - Pu Gao; Kuan Li; Yuanxun Zheng (Advances in Civil Engineering)
The experimental work presents results on the fatigue performance of composite beams in the negative moment region and the changes of stiffness and deformation of composite beams under repeated loads; fatigue tests were carried out on two double-layer composite beams. The fatigue performance of composite beams with different reinforcement ratios under complete shear connection and the variation of deflection, strain of the reinforcement, strain of steel beam, and crack growth under fatigue load were obtained. The results showed that the fatigue resistance performance of concrete slab with low reinforcement ratio was much lower than that of concrete slab with high reinforcement ratio whereas, under the fatigue load, the stress of the welding nail in the negative moment region was small and the slip was almost negligible. The degradation of stiffness and the development of cracks were mainly due to the degradation of bond-slip between the concrete and reinforcement. The fatigue failure mode was the fracture of the upper reinforcement in negative moment region. The results obtained in this study are helpful in the design of composite beam.